The chemical profiling of Salvia plebeia during different growth periods and the biosynthesis of its main flavonoids ingredients - Dai, Yiqun; Ye, Ziyu; Liu, Hui; Zhu, Ruirui; Sun, Lanlan; Li, Shuai; Xie, Guoyong; Zhu, Yan; Zhao, Yucheng; Qin, Minjian (Frontiers in Plant Science, 2023)
Salvia plebeia (Lamiaceae) is a valuable medicinal plant widely distributed across Asia and Oceania. However, the composition and accumulation patterns of its active ingredients in different organs during the growth and their biosynthetic mechanism remain unknown. Therefore, we conducted metabolite profiling, transcriptomic analysis, and biological functional verification to explore the distribution, accumulation, and biosynthesis mechanisms of flavonoids in S. plebeia. We identified 70 metabolites including 46 flavonoids, 16 phenolic acids, seven terpenoids, and one organic acid, of which 21 were previously unreported in S. plebeia. Combining metabolomictranscriptomic analysis and biological functional verification, we identified the key genes involved in biosynthesis of its main active ingredients, hispidulin and homoplantaginin, including SpPAL,